Conventional PCR genotipification of resistance genes in Klebsiella pneumoniae ESBL producer isolated from clinical samples of the UCI service of two hospitals in Cajamarca (SCIÉNDO INGENIUM, 2021)
The objective was to genotypically determine by PCRc, the presence of the blaSHV, blaTEM and blaCTX-M genes, in K. pneumoniae producer of ESBL, of the ICU service of two hospitals in Cajamarca. In this study, different clinical biological samples were used, from which 59 strains of K. pneumoniae ESBL + were isolated, of which 37 (62.7%) strains correspond to the Regional Hospital of Cajamarca and 22 (37.3%) to the Hospital II Essalud Cajamarca. With respect to the production of resistance genes, in the Regional Hospital of Cajamarca 37/37 (100%) strains presented the blaSHV gene, 33/37 (89%) the blaTEM gene and 36/37 (97%) the blaCTX- M. In the Essalud Cajamarca II hospital, the presence of the blaSHV gene was 17/22 (77%) strains, blaTEM 20/22 (91%) and blaCTX-M 20/22 (91%). Performing the total statistical analysis at the level of hospitals of Cajamarca, the blaSHV gene is present in 54/59 (92%) of strains, the blaTEM gene in 53/59 (90%) and the blaCTX-M gene in 56/59 (95%) strains. It is therefore concluded that, in both hospitals of Cajamarca, antimicrobial resistance is high, which is mainly produced by the genes under study, especially for K. pneumoniae ESBL +, which encode extended spectrum beta-lactamases
Keywords: antimicrobial resistance, Betalactamases; genotyping and PCR; Electrophoresis